Comparative Analysis of the Construction Industry in the EU and the Arab States of the Persian Gulf (GCC): Its Impact on Economic Growth - Veres, Boglárka; Szőke, Brigitta; Malatyinszki, Szilárd; Dávid, Lóránt Dénes (Journal of Ecohumanism, 2024)
The construction industry plays a pivotal role in propelling global economic growth. This research examines the economic contributions of the construction sectors in the European Union (EU) and the Gulf Cooperation Council (GCC) region. The EU’s approach is characterised by a focus on sustainability-driven policies, including energy efficiency and circular economy practices. This is intended to foster economic resilience and alignment with international commitments such as the Paris Agreement. In contrast, the construction sector in the Gulf Cooperation Council (GCC) is driven by large-scale infrastructure projects and urbanisation, which are in turn fuelled by oil revenues. This emphasises the importance of diversification as a means of reducing economic volatility. By analysing regulatory frameworks, investment trends and technological innovations, the study demonstrates how the construction industry contributes to GDP growth, job creation and industrial development in both regions. Moreover, it investigates potential avenues for interregional collaboration, underscoring the capacity of sustainable construction practices and innovation to bolster economic stability and competitiveness within the global construction landscape. The study also highlights how circular economy principles can redefine sustainable construction practices, enhancing resource efficiency and promoting resilience.